BENTUK GERAK TARI TIKAR PURUN DI SANGGAR RADEN KUNING DESA SERI TANJUNG - Jannah, Miftahul; Diah Budi Setya Ningrum, Naomi; Ibrahim Banul Ngindom, Wahid (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Based on the results of this study, the Purun Mat Dance is a dance inspired by the activities of the people of Tanjung Atap Village, Tanjung Batu District, Ogan Ilir Regency, in processing purun into woven mats. The results of the Purun Mat Dance research based on Y. Sumandiyo Hadi's concept are: (1) Unity. The unity of the Purun Mat dance movement form can be seen from the aspects of movement, space, and time. (2) Variations of the Tikar Purun dance are found in the form of various movements of harvesting, weaving purun mats, ungkel side up (3) Repetition or repetition in the Tikar Purun dance there are several repetitions consisting of various forms of ungkel sitting, ungkel, mendhak, ungkel mendhak, mbaya mangap, wipe sweat, stretch to the side up, ungkel side up (4) Transitional movements of changing places in the Tikar Purun dance are found in the form of various movements of Swinging, Harvesting purun, and rotating (5) There are 29 series of dance movements that have been explained in the name of the movement forms that have been arranged through the initial, middle and final movements (6) Comparison in the Movement Forms of the Tikar Purun Dance is not done (7) The climax of the Tikar Purun dance can be seen from the various movements of harvesting, drying, pounding, weaving, rotating, and ending in mendhak stretching purun (selling purun).